Dynamics of Phyto- and Bacterioplankton in Southern Baikal and Irkutsk Reservoir During the Open Water Period of 2023 According to Metabarcoding Data - Yuri Galachyants; Darya Petrova; Artem Marchenkov; Maria Nalimova; Yelena Likhoshway (Diversity)
Artificial reservoirs formed by hydroelectric dams are young ecosystems requiring water quality monitoring, as they often serve local populations. Traditionally, this is performed through hydrochemical and sanitary assessments, alongside phytoplankton composition analysis. This study aimed to assess the seasonal dynamics of microbial communities—both bacterioplankton and microeukaryotes including phytoplankton—in the Irkutsk Reservoir (IR), which is fed by the cold oligotrophic waters of Southern Baikal (SB). Using parallel metabarcoding of 16S and 18S rRNA gene fragments, we analyzed community composition during the open-water season and evaluated the ecological connectivity between these two freshwater systems. We demonstrated that seasonal changes in microeukaryotic communities were closely linked between SB and IR, with the greatest divergence observed in early summer and progressive convergence by autumn. Metabarcoding confirmed microscopy-based observations while providing higher taxonomic resolution and detecting otherwise overlooked groups. Bacterioplankton communities also exhibited seasonal variation and were shaped by environmental gradients and reservoir characteristics. Cyanobacteria peaked in SB in late summer but did not dominate communities, unlike in mesotrophic lowland reservoirs. These findings demonstrate the value of metabarcoding for freshwater monitoring and provide new insights into microbial community dynamics in river–reservoir systems influenced by oligotrophic lake inflow.